Mapping autoantibody targets of full-length C-reactive protein in systemic lupus erythematosus: importance for neutrophil function and classical complement activation - Karlsson, Jesper; Wirestam, Lina; Duàn, Hanna; Ahmad, Suhana; Appelgren, Daniel; Enocsson, Helena; Wetterö, Jonas; Sjöwall, Christopher (Frontiers in Immunology, 2025)
C-reactive protein (CRP) is an important pattern recognition molecule of innate immunity. Autoantibodies targeting CRP are common in patients with systemic lupus erythematosus (SLE) and the levels correlate with disease activity. The purpose of this study was to investigate binding sites of IgG autoantibodies on the full linear sequence of CRP and identify potential associations with clinical variables in well-characterized SLE patients; a secondary aim was to investigate the effect of an epitope-based synthesized peptide motif on neutrophil functions. The levels of anti-CRP and SLE-associated antibodies were assessed, and a microarray-based linear epitope mapping was performed to detect binding sites on the full CRP monomer. We observed that anti-CRP antibodies bind to a variety of linear epitopes with a higher prevalence in SLE compared to healthy blood donors. Eleven unique epitopes were identified, of which five were found exclusively in SLE. Furthermore, we show that patients with anticardiolipin IgG and/or anti-β2GPI IgG antibodies have a higher number of positive CRP epitopes, and some CRP autoantibody-specificities associate with antiphospholipid antibodies, disease activity, and classical complement activation. In addition, one identified motif was selected, synthesized, and used for studying neutrophil function. This peptide showed modulatory capacity on neutrophil oxidative burst and chemotaxis, but not on neutrophil extracellular trap formation. Our results implicate a wide variation of anti-CRP autoantibody binding motifs of the linear structure of CRP in SLE patients. Some epitopes have the potential to modify innate host responses of relevance to the pathogenesis of SLE.